Perancangan dan Pengembangan Sistem Point of Sale untuk Manajemen Penjualan dan Inventaris: Studi Kasus di Purna Sembako - Dinar Rahayu; Bagas Dwi Nugroho; Linda Apriyanti; Bening Fathima Rabbaniya Amatillah (Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2025)
This study aims to design and develop a Point of Sale (POS) system tailored to the operational needs of Purna Sembako, a micro retail business located in a rural area. The main issue addressed is the store’s continued use of manual transaction recording, which causes inefficiency, data entry errors, and delays in reporting. The research follows a Research and Development (R&D) approach using software engineering methods. The development process includes needs analysis, web-based system design, implementation of transaction recording, inventory management, and sales reporting features. Black box testing was employed to validate system functionality, while user evaluation was conducted using a Likert-scale questionnaire involving the store owner and staff to assess usability, efficiency, and user satisfaction. The testing results indicate that the system operates as intended, and user evaluations rated the system as “Good” to “Very Good” across all aspects. The developed POS system proved effective in improving operational efficiency and data accuracy, while also contributing to digital transformation in small-scale retail enterprises.